Preparation of Cu/ZrW2O8 structures by chemical deposition from formaldehyde-free solution. (2nd January 2022) - Mirchev, N.; Lazarova, D.; Georgieva, M.; Petrova, M.; Tachev, D.; Avdeev, G.
ABSTRACT: This paper presents the process of preparation and characterisation of chemically deposited copper coatings on ZrW2 O8 particles. The interest in this topic is driven by the possibility of using such a material in the preliminary stage of obtaining metal-ceramic composites of Cu/ZrW2 O8 type with low or zero CTE (coefficient of thermal expansion). A method for deposition of copper coatings from formaldehyde-free solution with low alkalinity (pH 9.0) at two temperatures 75°С or 80°С is described. Some properties of the composite material are compared to those of samples obtained from formaldehyde-containing solution with high alkalinity (pH 13) at 45°C. Three different methods of homogenisation of the solution have been applied: by air bubbling, by ultrasound and by both (combined method). Their influence on the properties of the copper coatings has been investigated.